Measure Underachievement’s in the Space of Livelihoods through Artificial Intelligence - Sengupta, Soumya; Singh, Dharmpal (International Journal of Computer Sciences and Engineering, 2026)
Ensuring a sustainable livelihood to the larger counts of the population is the most challenging agenda of any developing country. So this work wants to quantify the level of under achievements of different economies in the field of sustainable livelihood. The contribution of influencing variables of under-achievement and contributing variables to achievement in the construction of under achievement livelihood space is also determined under this work. The interaction between these two types of variables and their juxtaposed effects are evaluated through the use of artificial neural network. Finally this method of artificial intelligence is used to achieve a self-sustained monotonic high rate of development. The whole work is presented through a set theoretic approach which is followed by the testing of the same. It is expected that the application of neural network in the process of self-sustained growth of sustainable livelihood is unique in academic discourse